PENGARUH KECEMASAN TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS DI WILAYAH PUSKESMAS BANYUANYAR SURAKARTA - Murdiningsih, Dyah Surti; Ghofur, Gun Gun Abdul (TALENTA, 2013)
Health problems tend to increase, mental health is an issue that most real improvement. Some physical illnesses can cause anxiety in a person. A person with a chronic disease, prone to anxiety sufferers Diabetes is one of them. Â  The purpose of this study is the effect of anxiety on blood glucose levels in people with diabetes mellitusÂ  inÂ  SurakartaÂ  BanyuanyarÂ  RegionalÂ  Health Center.Â  HypothesisÂ  There is a positive effect of anxiety on blood glucose levelsÂ  in people with diabetes mellitusÂ  in the PHC Banyuanyar Surakarta. Â  InÂ  this studyÂ  sample wasÂ  respondents with Diabetes MellitusÂ  (DM)Â  type 2Â  Surakarta region Banyuanyar Health Center. ByÂ  samplingÂ  theÂ  totalÂ  sampling withÂ  gaugeÂ  ScaleÂ  anxiety scale and blood glucose levels of people with Diabetes Mellitus (DM) Type 2. Â  BasedÂ  on calculations using theÂ  computer programÂ  SPSSÂ  15.0 for WindowsÂ  obtained the value of rÂ  count (0.754)> rÂ Â  table (0.339) or (p = 0.000 <0.05) so that HaÂ  is accepted,Â  it meansÂ  a significant differenceÂ  betweenÂ  theÂ  levels ofÂ  anxietyÂ  bloodÂ  glucoseÂ  in patients with diabetes mellitus in the Greater Surakarta Banyuanyar Health Center. Â Â  Distribution results based on Blood Glucose Levels of respondents can be seen that the mostÂ  dominantÂ  isÂ  the Blood GlucoseÂ  LevelsÂ  respondentsÂ  inÂ  the category DMÂ  (â¥Â  200)Â  that is equal to 16 or 47.1%.